Analisis Pesn Edukasi yang Terkandung dalam Akun Tiktok @oBenKa Sebagai Layanan Bimbingan Konseling Bagi Remaja - Nor Khofifatus Solehah (AflahConsilia : Jurnal Bimbingan dan Konseling, 2026)
The advancement of information and communication technology in the digital era has transformed the way society, particularly adolescents, accesses and utilizes knowledge resources. Social media has evolved from a mere entertainment platform into a potent educational space. One widely favored platform is TikTok, especially the account @oBenKa, which consistently delivers content on self-development, psychological well-being, motivation, and adolescent social life. This study aims to identify and examine the educational messages in the TikTok account @oBenKa from the perspective of guidance and counseling services for adolescents. A qualitative approach based on library research was employed, using Philipp Mayring's content analysis model through the stages of reduction, categorization, and data interpretation. The findings reveal that the educational messages in the account encompass four dimensions of guidance and counseling services: personal, social, academic, and career. These messages carry values of self-recognition, emotional regulation, confidence building, social competence, learning motivation, and future orientation aligned with adolescent developmental tasks. These results indicate that the TikTok account @oBenKa has the potential to serve as an educational medium as well as an innovative and contextual guidance and counseling tool for the digital generation.